Impact of morbid obesity on the kidney function of patients with type 2 diabetes. Issue 1 (April 2015) - Belhatem, Narimène; Mohammedi, Kamel; Rouzet, François; Matallah, Nadia; Al Baloshi, Ahmed; Travert, Florence; Velho, Gilberto; Roussel, Ronan; Le Guludec, Dominique; Marre, Michel; Hansel, Boris
Highlights Urinary albumin excretion increased with obesity stages. Morbid obesity increases the risk of micro- and macroalbuminuria. Adjusted glomerular filtration rate declined with obesity stages. Morbid obesity interacts with type 2 diabetes to impair kidney function.